Gambaran Kepuasan Tenaga Kesehatan terhadap E-Puskesmas dengan Metode PIECES di Puskesmas Waruroyom Tahun 2026 - Yuniya Maghfiroh; Yanto Haryanto; Bhakti Aryani; Fitria Dewi Rahmawati (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Background: The Waruroyom Community Health Center has implemented the E-Puskesmas application as an information system to support recording, service data management, and health reporting. Initial observations revealed constraints such as network disruptions, suboptimal data input processes, and differences in users' ability to operate the system, which affected health workers' satisfaction. Methods: This research used a quantitative descriptive approach with a population of 47 health workers at Waruroyom Community Health Center, all of whom were included as samples (total sampling). Data were collected using a Likert scale questionnaire based on the six dimensions of the PIECES method. Results: All six PIECES dimensions fell within the satisfied category, with mean scores ranging from 3.83 to 4.10. The Information dimension obtained the highest mean (4.10), while the Performance dimension obtained the lowest mean (3.83). The highest satisfaction indicator across all dimensions was information accuracy (89.3%), while the lowest was the indicator of systems rarely experiencing errors (44.6%). Discussion: The strength of E-Puskesmas lies in its information quality, while technical stability remains a primary challenge. Conclusions: Health workers at Waruroyom Community Health Center are satisfied with E-Puskesmas in all six PIECES dimensions. Improvements are needed particularly in the Performance dimension, especially in minimizing system errors and strengthening technical support services.